Konsepsi Negara Dalam Islam (Sebuah Diskursus Politik Hukum Islam) - Iskandar, Iskandar (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
The Qur'an introduces Islam as ad din, therefore, Islam is not just a "religion" in the narrow sense, but covers all aspects of human life. in ad-din al Islam, humans are required to menggayutkan all its activities, either born or spiritual to the supreme absolute reality, that is God Almighty. Being a Muslim, meaning, expression forever subservient and obedient to Allh SWT, devote yourself to Him.The teachings of Islam, he said, ordered to consider the interests of minorities, recognize their rights, especially all the rights included in the circle of human rights. in the concept of this country as the reference is the Qur'an and Sunnah. Thus requiring an ijtihad to review it.Countries in the Islamic perspective, if explored further in fact no concept of the state in the Qur'an Q.S. Ali Imran (3): 140, Q.S. Al-Hashr (59): 7, Q.S. Al Bagarah (2): 213, Q.S. Shura (42): 38, Q.S. An Nisa (4), while the Government of the Prophet with a combination of the people of the Ansar and muhajrin an early milestone of unity and brotherhood, as well as other people are tribes that are in the Medina area in conducting their activities as social beings with their charter Medina. This union covers all aspects of life.